Proposta de plano de implantação do BIM na indústria da construção civil - Böes, Jeferson Spiering (2019)
The implementation of the Builiding Information Model (BIM) has been incipient and concentrated in a small number of companies in the construction sector. Several studies have been implemented, with BIM support and consolidation for organizations, usually with an operational focus, with little emphasis on the vision of implementation in a macro sector. BIM deployment should be phased in, including a set of policies, processes, and technologies in organizations. This objective, the present work have a purpose rational method, BIM and the civil building in the civil market, in the storages of development of real estate investments. Compared to BIM in Brazil, the work is characterized as an exploratory study with a qualitative approach. A research strategy adopted for this work is the Desing Scientific Research (DSR), proposed for a work methodology in construction. This research is divided in two moments. The first one includes the diagnosis of the characterization of BIM use, adoption and maturity in the state of Ceará. This stage involved more than 201 stakeholders, through questionnaires and interviews, covering stakeholders from all over the state. There were also 11 BIM maturity models for use, as well as it was developed to measure BIM maturity for Higher Education Institutions, due to a gap in the literature. Identifying stakeholders who can help improve local performance and serve as a benchmark for measuring the performance of the proposed plan. The BIM for the construction of the state of Ceará, with the purpose of implementing adoption strategies, such as Builders, Designers, as Higher Education Institutions and the Government. The BIM implementation plan is structured based on BIM BR, having the entire set of 45 national spheres, divided into 8 components of BIM Macro Maturity. Strategic actions are divided into three phases, based on BIM's implementation plan, implementation and continuous improvement through BIM's maturity.